THE ROLE OF HIGHER EDUCATION IN SHAPING THE POLITICAL ASPIRATIONS OF STUDENTS, STATE ISLAMIC UNIVERSITY OF NORTH SUMATRA - Alya Qais Tsaabitah; Junaidi (SOSIOEDUKASI, 2026)
Higher education serves a fundamental role that extends far beyond the mechanistic boundaries of technical knowledge transfer, acting instead as a primary engine in reconstructing the critical consciousness and political aspirations of students, particularly female students within State Islamic Higher Education Institutions (PTKIN). This study aims to comprehensively dissect how the academic and social ecosystem at the State Islamic University (UIN) of North Sumatra influences the trajectory of female students' political aspirations amidst the intersection of conventional theological doctrines and contemporary liberal democratic demands. Utilizing a qualitative paradigm with a phenomenological approach, this research seeks to capture the essence of female students' lived experiences in navigating campus power structures through in-depth interviews with purposively selected informants. Data analysis was conducted using triangulation techniques involving 30 scientific references to ensure interpretative validity over the narratives generated from the research field. Empirical findings indicate that progressive fiqh siyasah-based curriculum interventions and participation in student organizations have successfully transformed apathy into active political agency, despite systemic resistance from remnants of patriarchal culture that legitimize women's subordination through narrow interpretations of sacred texts. The study also reveals a "agency transition" phenomenon where female students have begun utilizing digital literacy as an instrument of resistance against political marginalization within the campus public sphere. This research concludes that strengthening gender-justice-oriented political education must be synergized with concrete institutional affirmative policies to ensure that the leadership potential of female students is not eroded by rigid patriarchal morality standards.